Preparing Rural and Regional Students for the Future World Of Work: Developing Authentic Career Focussed Curriculum Through a Collaborative Partnership Model - Woodroffe, Jessica; Kilpatrick, Sue; Williams, Brett; Jago, Matthew (Australian and International Journal of Rural Education, 2017)
Small places are not devoid of opportunities nor of successful programs to equip them for the future, despite perception to the contrary (West, 2013). This paper considers career education in the context of rural places in the modern globalised world. The paper introduces the Pathways to Success project, involving more than eighty initiatives mapped to the Australian curriculum showcasing further education, training and careers in local industries to more than 8000 learners and their schools and teachers in Tasmania. It outlines how a partnership model among schools, industry, technical and vocational, and higher education sectors can be used to move from a sole dependency model to a partnership model of career education. Drawing on the project's mixed method evaluation results, the paper considers the key opportunities and challenges for preparing rural and regional Tasmanian students for the future world of work. It focuses on how collaborative partnerships can better equip educators with information and networks they need to positively impact on how young rural and regional Tasmanian students consider education pathways and career options to get to 'what's next' in their lives. It showcases how rural and regional communities and resources can be used to develop new and innovative place based career and curriculum learning.